Development of an in situ synchrotron X‐ray total scattering setup under pressurized hydrogen gas. Issue 3 (25th May 2018) - Sakaki, Kouji; Kim, Hyunjeong; Machida, Akihiko; Watanuki, Tetsu; Katayama, Yoshinori; Nakamura, Yumiko
Abstract : An in situ synchrotron X‐ray total scattering setup has been developed that allows observation of the phase transformation in hydrogen storage materials upon hydrogenation. This setup can be used to study the change in average and local structures during hydrogen absorption–desorption reactions. Abstract : This article describes the development of an in situ gas‐loading sample holder for synchrotron X‐ray total scattering experiments, particularly for hydrogen storage materials, designed to collect diffraction and pair distribution function (PDF) data under pressurized hydrogen gas. A polyimide capillary with a diameter and thickness of 1.4 and 0.06 mm, respectively, connected with commercially available Swagelok fittings was used as an in situ sample holder. Leakage tests confirmed that this sample holder allows 3 MPa of hydrogen gas pressure and 393 K to be achieved without leakage. Using the developed in situ sample holder, significant background and Bragg peaks from the sample holder were not observed in the X‐ray diffraction patterns and their signal‐to‐noise ratios were sufficiently good. The PDF patterns showed sharp peaks in the r range up to 100 Å. The results of Rietveld and PDF refinements of Ni are consistent with those obtained using a polyimide capillary (1.0 mm diameter and 0.04 mm thickness) that has been used for ex situ experiments. In addition, in situ synchrotron X‐ray total scattering experiments under pressurized hydrogen gas up to 1 MPa were successfully demonstrated for LaNi4.6 Cu.